A preparation method and application of zinc hyaluronate
Through a new preparation method, sodium hyaluronate is mixed with zinc chloride aqueous solution, adjust the pH and temperature, add promoters and hydrochloric acid solution, and finally prepare zinc hyaluronate particles by precipitation of anhydrous ethanol and vacuum drying, solving the problem of In the existing methods, the preparation of zinc ion content and long production cycles are achieved, and zinc hyaluronate particles with high zinc and low sodium and high light transmittance are achieved.
Patent Information
- Application Number
- CN202311480051.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-11-08
AI Technical Summary
The existing methods for preparing zinc hyaluronate have problems such as low zinc ion content, long production cycle, complex process, many equipment, low yield, high sodium ion content and low light transmittance in the product.
Use sodium hyaluronate to mix with deionized water, stir until completely dissolved, then mix with zinc chloride aqueous solution, adjust the pH to 5-5.5, warm up and stir, add promoter and hydrochloric acid solution, continue stirring and adjusting the pH, and finally pass Precipitation of anhydrous ethanol and vacuum drying to produce zinc hyaluronate granules.
It increases the zinc content in zinc hyaluronate, reduces the sodium content, increases the light transmittance, simplifies the separation and purification steps, reduces production costs, and is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a preparation method of zinc hyaluronate and application thereof. Background Art
[0002] Sodium hyaluronate, also known as sodium hyaluronate, is a polysaccharide composed of repeated connection of glucuronic acid and aminoglucose disaccharide units. It is one of the main components of the extracellular matrix of the skin. It has extremely high hydrophilicity and viscoelasticity and is known as an ideal natural moisturizing factor. When applied to the skin surface, sodium hyaluronate not only has moisturizing and lubricating effects, but also has physiological effects such as nutrition, repair and damage prevention. It is a non-toxic, non-immunogenic, non-inflammatory biomaterial with good biodegradability and compatibility. Zinc, as an indispensable trace element for the human body, can play a pivotal role in the body's sexual development, sexual function, and the generation of germ cells. Moreover, zinc is an important component of more than 200 enzymes in the body, which is related to brain development and intelligence. It also promotes lymphocyte proliferation and activity. It is useful for maintaining normal epithelial and mucosal tissues, defending against bacterial and viral invasion, promoting wound healing, reducing skin lesions such as acne, and correcting taste failure.
[0003] Zinc hyaluronate is the zinc salt of hyaluronic acid, a complex formed by the reaction of sodium hyaluronate and zinc salt reagent. It has the biological activity of sodium hyaluronate and zinc elements and has good synergistic effects. Zinc hyaluronate can be used as a health food such as capsules or solutions. It can provide zinc elements to the human body through oral administration or application, and can greatly improve the absorption of hyaluronic acid in the human body. It can also be used to promote the healing of corneal injuries, healing of diabetic foot wounds, antimicrobial activity, antioxidant and anti-oxidative damage, treatment of burns, and treatment of peptic ulcers.
[0004] At present, the main method for preparing zinc hyaluronate is ion exchange method, which is mainly divided into two types. The first is the ion exchange method in solution state, in which hyaluronic acid is dissolved and then placed on an ion exchange column to convert Na-HA into Zn-HA, and then precipitated with ethanol and dehydrated to obtain the product. This method has a high zinc ion content, but the production cycle is long, the process is complicated, the equipment used is large, and the yield is low; or Na-HA is dissolved in water, precipitated with an organic solvent after adding zinc salt, and then dehydrated with an organic solvent to obtain the product. Although the path of this method is simple, the sodium ion content in the product is high. The second is the ion exchange method in solid state, in which the zinc salt is first dissolved in a certain concentration of alcohol-water solution, Na-HA powder is added, and the replacement reaction is completed in solid state. This method is simple to operate, has low production cost, high yield, high zinc content and low sodium content in the product, and has certain advantages, but the transmittance of large molecular weight products is low. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing zinc hyaluronate and application thereof. The reaction process is mild, the separation and purification steps are simple, the production cost is low, and the method is suitable for industrial production. The prepared zinc hyaluronate has a high zinc content and a low sodium content, can be quickly dissolved in a solution, and has a high light transmittance.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing zinc hyaluronate comprises the following steps: mixing sodium hyaluronate and deionized water, stirring at a stirring speed of 100-300 rpm at room temperature until the mixture is completely dissolved, thereby obtaining a sodium hyaluronate solution; dissolving zinc chloride in deionized water, stirring evenly, thereby obtaining a zinc chloride aqueous solution; mixing the zinc chloride aqueous solution with the sodium hyaluronate solution, stirring at a stirring speed of 100-300 rpm at room temperature for 10-30 minutes, adding a hydrochloric acid solution to adjust the pH to 5-5.5, heating the mixture to 40-45° C., stirring the mixture for 3-4 hours, adding an accelerator, and adding a hydrochloric acid solution to continue adjusting the pH to 4-4.5, continuing stirring for 2-3 hours, filtering, and then adding anhydrous ethanol to the filtrate for precipitation until no agglomeration occurs, washing the precipitate 2-3 times with anhydrous ethanol of 2-3 times the volume of the precipitate, dehydrating the precipitate, granulating the precipitate, and then vacuum drying the precipitate at 50-60° C. for 7-8 hours, thereby obtaining a zinc hyaluronate granule product;
[0008] The molecular weight of sodium hyaluronate in the sodium hyaluronate solution is 400-1000KDa;
[0009] The mass volume ratio of sodium hyaluronate and deionized water in the sodium hyaluronate solution is 10-50 g: 200-2000 mL;
[0010] The mass volume ratio of zinc chloride to deionized water in the zinc chloride aqueous solution is 1.7-13.58 g:20-50 mL;
[0011] The mass ratio of sodium hyaluronate in the sodium hyaluronate solution, zinc chloride in the zinc chloride aqueous solution, and accelerator is 10-50:1.7-13.58:0.6-0.7;
[0012] The mass fraction of the hydrochloric acid solution is 18-22%;
[0013] The addition rate of the anhydrous ethanol is 8-10 g / min;
[0014] The preparation method of the promoter comprises the following steps: adding zeolite powder to a first zinc chloride aqueous solution, stirring at a stirring speed of 60-120 rpm at 40-60° C. for 40-60 min, filtering, washing the filter residue with deionized water for 2-3 times, mixing the washed filter residue with a sodium alginate aqueous solution, stirring at a stirring speed of 60-120 rpm at 30-50° C. for 40-60 min, filtering, washing the filter residue with deionized water for 2-3 times; then mixing the washed filter residue with a second zinc chloride aqueous solution, stirring at a stirring speed of 60-120 rpm at 40-60° C. for 40-60 min, filtering, washing the filter residue with deionized water for 2-3 times, and vacuum drying at 60-70° C. for 4-5 h to obtain the promoter;
[0015] In the preparation of the accelerator, the mass fraction of the first zinc chloride aqueous solution is 9-10%;
[0016] The mass fraction of sodium alginate aqueous solution is 2.5-3%;
[0017] The mass fraction of the second zinc chloride aqueous solution is 7-8%;
[0018] The mass ratio of zeolite powder, the first zinc chloride aqueous solution, the sodium alginate aqueous solution, and the second zinc chloride aqueous solution is 10-12:120-130:130-150:90-100;
[0019] The particle size of the zeolite powder is 80-120 meshes.
[0020] An application of zinc hyaluronate prepared by the aforementioned preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The preparation method of zinc hyaluronate of the present invention can increase the zinc content in zinc hyaluronate and reduce the sodium content. The zinc content in the prepared zinc hyaluronate is 9.95-10.22%, the sodium content is 0.16-0.21%, and the light transmittance is 99.4-99.9%;
[0023] (2) The preparation method of zinc hyaluronate of the present invention adopts a granulation process to prepare zinc hyaluronate into zinc hyaluronate granules, thereby preventing the generation of small particle dust and allowing rapid dispersion and dissolution into liquid, thereby saving time and cost;
[0024] (3) The method for preparing zinc hyaluronate of the present invention can promote cell proliferation, increase the protein content in cells, reduce the lipid content in cells, and achieve a firming effect. DETAILED DESCRIPTION
[0025] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0026] Example 1
[0027] A method for preparing zinc hyaluronate, specifically comprising:
[0028] 10 g of sodium hyaluronate with a molecular weight of 1000 KDa and 2000 mL of deionized water were added to a 5000 mL reaction bottle, and the mixture was stirred at a stirring speed of 100 rpm at room temperature until it was completely dissolved to obtain a sodium hyaluronate solution. 1.7 g of zinc chloride was dissolved in 20 mL of deionized water, and the mixture was stirred evenly. The mixture was added to a 5000 mL reaction bottle and mixed with the sodium hyaluronate solution. The mixture was stirred at a stirring speed of 100 rpm at room temperature for 10 min, and then a hydrochloric acid solution with a mass fraction of 18% was added to adjust the pH to 5. 5. Then, the temperature was raised to 40°C, stirred for 3 hours, and then 0.6 g of accelerator was added, and a hydrochloric acid solution with a mass fraction of 18% was added to continue to adjust the pH to 4, and the stirring was continued for 3 hours, filtered, and then anhydrous ethanol was slowly added to the filtrate for precipitation, and the addition rate was controlled to be 8 g / min, until no agglomeration was produced, and the precipitate was washed twice with anhydrous ethanol with a volume of 2 times the precipitation volume, and then dehydrated and granulated, and then the obtained particles were placed at 50°C for vacuum drying for 8 hours to obtain 10.5 g of hyaluronate zinc granule product;
[0029] The preparation method of the promoter is as follows: 10g of zeolite powder is added to 120g of a zinc chloride aqueous solution with a mass fraction of 9%, stirred at 40°C at a stirring speed of 60rpm for 40min, filtered, and the filter residue is washed twice with deionized water, the washed filter residue is mixed with 130g of a sodium alginate aqueous solution with a mass fraction of 2.5%, stirred at 30°C at a stirring speed of 60rpm for 40min, filtered, and the filter residue is washed twice with deionized water; then the washed filter residue is mixed with 90g of a zinc chloride aqueous solution with a mass fraction of 7%, stirred at 40°C at a stirring speed of 60rpm for 40min, filtered, the filter residue is washed twice with deionized water, and dried at 70°C to obtain the promoter;
[0030] The particle size of the zeolite powder is 80 mesh;
[0031] After testing, the zinc content in the hyaluronic acid zinc granule product is 9.95%, the sodium content is 0.21%, the molecular weight is 740KDa, and the transmittance is 99.4%.
[0032] Example 2
[0033] A method for preparing zinc hyaluronate, specifically comprising:
[0034] 10 g of sodium hyaluronate with a molecular weight of 400 KDa and 200 mL of deionized water were added to a 5000 mL reaction bottle, and stirred at a stirring speed of 200 rpm at room temperature until completely dissolved to obtain a sodium hyaluronate solution; 2.7 g of zinc chloride was dissolved in 20 mL of deionized water, stirred evenly, and added to a 5000 mL reaction bottle and mixed with the sodium hyaluronate solution. After stirring at a stirring speed of 200 rpm at room temperature for 20 minutes, a 20% hydrochloric acid solution was added to adjust the pH to 5.2, and then The mixture was heated to 42°C and stirred for 3.5 hours, then 0.6 g of an accelerator was added, and a 20% hydrochloric acid solution was added to continue adjusting the pH to 4.2, and the mixture was stirred for 2.5 hours. The mixture was filtered, and then anhydrous ethanol was slowly added to the filtrate for precipitation. The addition rate was controlled to be 9 g / min. The precipitate was washed three times with anhydrous ethanol twice the volume of the precipitate, and then dehydrated and granulated. The obtained granules were then dried under vacuum at 55°C for 7.5 hours to obtain 11.3 g of a zinc hyaluronate granule product.
[0035] The preparation method of the promoter is as follows: 11g of zeolite powder is added to 125g of a zinc chloride aqueous solution with a mass fraction of 9.5%, stirred at 50°C at a stirring speed of 100rpm for 50min, filtered, and the filter residue is washed twice with deionized water, the washed filter residue is mixed with 140g of a sodium alginate aqueous solution with a mass fraction of 2.8%, stirred at 40°C at a stirring speed of 100rpm for 50min, filtered, and the filter residue is washed twice with deionized water; then the washed filter residue is mixed with 95g of a zinc chloride aqueous solution with a mass fraction of 7.5%, stirred at 50°C at a stirring speed of 100rpm for 50min, filtered, the filter residue is washed twice with deionized water, and dried at 75°C to obtain the promoter;
[0036] The particle size of the zeolite powder is 100 mesh;
[0037] After testing, the zinc content in the hyaluronic acid zinc granule product is 9.80%, the sodium content is 0.16%, the molecular weight is 290KDa, and the transmittance is 99.9%.
[0038] Example 3
[0039] A method for preparing zinc hyaluronate, specifically comprising:
[0040] Add 50 g of sodium hyaluronate with a molecular weight of 400 KDa and 2000 mL of deionized water to a 5000 mL reaction bottle, stir at room temperature at a stirring speed of 300 rpm until completely dissolved to obtain a sodium hyaluronate solution; dissolve 13.58 g of zinc chloride in 50 mL of deionized water, stir evenly, add to a 5000 mL reaction bottle and mix with the sodium hyaluronate solution, stir at room temperature at a stirring speed of 300 rpm for 30 min, and then add a 22% hydrochloric acid solution to adjust the pH to 5. 5. Then, the temperature was raised to 45°C, stirred for 4 hours, and then 0.7 g of accelerator was added, and a 22% hydrochloric acid solution was added to continue to adjust the pH to 4.5, and the stirring was continued for 2 hours. After filtering, anhydrous ethanol was slowly added to the filtrate for precipitation, and the addition rate was controlled to be 10 g / min. When no agglomeration was produced, the precipitate was washed three times with anhydrous ethanol of 3 times the volume of the precipitate, and then dehydrated and granulated. Then, the obtained granules were placed at 60°C for vacuum drying for 7 hours to obtain 56.4 g of hyaluronate zinc granules;
[0041] The preparation method of the promoter is as follows: 12g of zeolite powder is added to 130g of a 10% zinc chloride aqueous solution, stirred at 60°C at a stirring speed of 120rpm for 60min, filtered, and the filter residue is washed 3 times with deionized water, the washed filter residue is mixed with 150g of a 3% sodium alginate aqueous solution, stirred at 50°C at a stirring speed of 120rpm for 60min, filtered, and the filter residue is washed 3 times with deionized water; then the washed filter residue is mixed with 100g of an 8% zinc chloride aqueous solution, stirred at 60°C at a stirring speed of 120rpm for 60min, filtered, the filter residue is washed 3 times with deionized water, and dried at 80°C to obtain the promoter;
[0042] The particle size of the zeolite powder is 120 mesh;
[0043] After testing, the zinc content in the hyaluronic acid zinc granule product is 10.22%, the sodium content is 0.17%, the molecular weight is 260KDa, and the transmittance is 99.5%.
[0044] Comparative Example 1
[0045] The same preparation method of zinc hyaluronate as in Example 3 was adopted, except that: "adding a 22% hydrochloric acid solution by mass to adjust the pH to 5.5" and "adding a 22% hydrochloric acid solution by mass to continue adjusting the pH to 4.5" were omitted, that is, no hydrochloric acid solution was added during the reaction to adjust the pH;
[0046] The obtained zinc hyaluronate granule product has a zinc content of 7.20%, a sodium content of 2.25%, a molecular weight of 280 KDa, and a light transmittance of 99.5%.
[0047] Comparative Example 2
[0048] The same method for preparing zinc hyaluronate as in Example 3 was adopted, except that the addition of the accelerator was omitted during the reaction;
[0049] The obtained zinc hyaluronate particle product has a zinc content of 7.94%, a sodium content of 3.72%, a molecular weight of 270 KDa, and a light transmittance of 99.1%.
[0050] It can be seen from the test results of Examples 1-3 and Comparative Examples 1-2 that by controlling the pH in stages, it is possible to avoid the occurrence of zinc hydrolysis side reactions that lead to a decrease in the efficiency of the positive reaction, a decrease in the zinc content, and an increase in the sodium content;
[0051] The promoter has zeolite powder as its core. After zinc ions are adsorbed on the zeolite powder, sodium alginate is added to complex with the zinc ions to form microspheres wrapped on the surface of the zeolite powder. Finally, it is treated with zinc ions to ensure that the sodium alginate can be completely complexed. When added to the reaction, it can provide a large specific surface area for the reaction, thereby promoting the reaction. In addition, it can also combine with some sodium ions and release zinc ions, thereby increasing the zinc content in the hyaluronic acid zinc particle product and reducing the sodium content.
[0052] Test example
[0053] The hyaluronic acid zinc particle product of Example 3 was tested for firming efficacy. The specific efficacy testing method is as follows:
[0054] Test for promoting cell proliferation: The test is based on fibroblasts. The fibroblasts used were provided by Guangdong Boxi Biotechnology Co., Ltd. The cell viability and cell proliferation were detected by the MTT method. The hyaluronate zinc particle product prepared in Example 3 was used as the test sample. The concentration gradient of the test sample was set to 5 μg / mL, 3 μg / mL, and 1 μg / mL. 2% NBS was used as the blank control, and 10% NBS was used as the positive control. MTT detection was performed at 24h, 48h, and 72h time gradients, respectively.
[0055] Fibroblasts were cultured at 3.5 × 10 3 The cells were inoculated into a 96-well plate at a density of 100 cells / well and incubated overnight in an incubator (37°C, 5% CO2). When the cell plating rate in the 96-well plate reached 30%, the cells were divided into groups for administration (i.e., the hyaluronate zinc particle product prepared in Example 3), and cultured in the incubator for 24h, 48h, and 72h, respectively, and the results were recorded.
[0056] After the cells were incubated for 24 hours, the supernatant was discarded, and MTT working solution (0.5 mg / mL, prepared immediately before use) was added. The cells were incubated at 37°C in the dark for 4 hours. After the incubation, the supernatant was discarded, 150 μL DMSO was added to each well, and the OD value was read at 490 nm. Similarly, the same MTT test was performed after 48 hours and 72 hours.
[0057] The test results showed that compared with the blank control group, the hyaluronic acid zinc particle product prepared in Example 3 had a significant promoting effect on the proliferation of fibroblasts at a concentration of 1 μg / mL 48 hours after administration, with an increase of 10.85%, and had no significant promoting effect on the proliferation of fibroblasts after 24 hours and 72 hours of administration; at a concentration of 3ug / mL, it had a significant promoting effect on the proliferation of fibroblasts 48 hours and 72 hours after administration, with an increase rate of 12.71% and 4.43%, respectively, and had no significant promoting effect on the proliferation of fibroblasts after 24 hours of administration; at a concentration of 5ug / mL, it had a significant promoting effect on the proliferation of fibroblasts 48 hours and 72 hours after administration, with an increase rate of 16.28% and 5.43%, respectively.
[0058] The above tests indicate that the zinc hyaluronate particle product prepared in Example 3 promotes cell proliferation at the corresponding test concentration and achieves the effect of tightening the skin.
[0059] Protein content increase test: The cells used in this test are fibroblasts, provided by Guangdong Boxi Biotechnology Co., Ltd. The firming effect of the sample to be tested is evaluated by detecting the changes in the content of type I collagen (Collagen I). The specific method is as follows:
[0060] The sample solution was prepared by the hyaluronate zinc particle product prepared in Example 3, and the hyaluronate zinc concentration was controlled to be 125 μg / mL, 12.5 μg / mL, and 1.25 μg / mL, respectively. When the cell plating rate in the 6-well plate reached 60%, group administration was carried out, 2 mL of sample was added to each well, and 3 replicates were set for each group. After the administration was completed, the 6-well plate was placed in an incubator (37° C., 5% CO ) and cultured for 24 h. Then, the cell culture supernatant was collected in an EP tube, placed in a -80° C. refrigerator for freezing, and detected according to the operating instructions of the Collagen I ELISA kit.
[0061] The test results showed that compared with the blank group, the Collagen I content of the hyaluronate zinc particle product prepared in Example 3 was significantly increased at concentrations of 125 μg / mL, 12.5 μg / mL and 1.25 μg / mL, with increase rates of 13.91%, 16.12% and 18.44%, respectively. It is believed that the hyaluronate zinc particle product prepared in Example 3 achieves the effect of skin tightening by increasing the Collagen I protein content at the corresponding test concentrations.
[0062] Similarly, the same test was carried out on the above-mentioned Example 1, Example 2 and Comparative Example 1, Comparative Example 2 at a concentration of 1.25 μg / mL, and the Collagen I enhancement rates were 16.8%, 17.5%, 11.68% and 12.75%, respectively.
[0063] Oil control efficacy test: Based on sebaceous gland cells, the oil control efficacy of the hyaluronic acid zinc particle product prepared in Example 3 was evaluated by detecting the lipid droplet content of sebaceous gland cells after the hyaluronic acid zinc particle product prepared in Example 3 was used. The specific test is as follows:
[0064] The cells used were sebaceous gland cells, provided by Guangdong Boxi Biotechnology Co., Ltd. The sample solution was prepared by the hyaluronate zinc particle product prepared in Example 3, and the hyaluronate zinc concentrations were controlled to be 125ug / mL, 25ug / mL, and 5ug / mL, respectively. 4 SZ95 cells were inoculated into 24-well plates at a density of 100 cells / well, and incubated overnight in an incubator (37°C, 5% CO2). When the cell plating rate in the 24-well plate reached 50%, the cells were divided into groups for drug administration, 1 mL was added to each well, and 3 replicates were set up in each group. After drug administration, the 24-well plate was placed in an incubator (37°C, 5% CO2) for 24 hours, and the oil red O staining method was used for detection. The fluorescence microscope was used for observation, and the detection was carried out at Ex: 450nm-500nm, Em: 515nm-560nm, and the photos were taken under a 200x microscope.
[0065] The test results show that the lipid content of the hyaluronate zinc particle product prepared in Example 3 was significantly reduced at the concentrations of 125 μg / mL, 25 μg / mL, and 5 μg / mL, indicating that the sample can reduce lipid droplet synthesis at the detected concentration, with inhibition rates of 11.18%, 8.9%, and 8.7%, respectively.
[0066] Similarly, the same test was performed on the above-mentioned Example 1, Example 3 and Comparative Example 1 and Comparative Example 2 at a concentration of 125 ug / mL, and the inhibition rates were 10.87%, 11.01%, 7.12% and 7.87%, respectively.
[0067] It can be seen from the above results that the hyaluronate zinc prepared in Example 1-3 can promote the production of collagen and achieve a certain firming effect on the skin. The hyaluronate zinc prepared in Example 3 has a promoting effect on the proliferation of fibroblasts at a certain test concentration and within a certain period of time, and achieves the effect of skin firming by proliferating fibroblasts. At the same time, no obvious cytotoxicity is shown within the concentration range of 0.125 mg / mL; the addition of the hyaluronate zinc prepared in Example 1-3 prepared in Example 1-3 within a certain concentration range significantly increases the collagen content in fibroblasts, and the increase rate is high, which promotes the production of collagen and achieves the purpose of firming the skin; at the same time, at different concentrations, the hyaluronate zinc prepared in Example 1-3 prepared in Example 1-3 can effectively inhibit the synthesis of fat droplets, reduce oil secretion, and have an oil control effect on the skin.
[0068] Unless otherwise specified, all percentages used in the present invention are by mass.
[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing zinc hyaluronate, characterized in that: Sodium hyaluronate and deionized water are mixed and stirred to obtain a sodium hyaluronate solution; zinc chloride is dissolved in deionized water and stirred to obtain a zinc chloride aqueous solution; the zinc chloride aqueous solution and the sodium hyaluronate solution are mixed and stirred, a hydrochloric acid solution is added to adjust the pH to 5-5.5, and then the temperature is raised to 40-45° C. and stirred, and then an accelerator is added, and a hydrochloric acid solution is added to continue to adjust the pH to 4-4.5, and the stirring is continued, and the mixture is filtered, and then anhydrous ethanol is added to the filtrate for precipitation until no agglomeration occurs, and the precipitate is washed with anhydrous ethanol, dehydrated, granulated, and vacuum dried to obtain a zinc hyaluronate particle product; The preparation method of the promoter comprises the following steps: adding zeolite powder to a first zinc chloride aqueous solution, stirring at 40-60°C, filtering, washing filter residues, mixing the washed filter residues with a sodium alginate aqueous solution, stirring at 30-50°C, filtering, washing filter residues; then adding the washed filter residues to a second zinc chloride aqueous solution, stirring at 40-60°C, filtering, washing the filter residues, and vacuum drying to obtain the promoter.
2. The method for preparing zinc hyaluronate according to claim 1, characterized in that: The molecular weight of the sodium hyaluronate in the sodium hyaluronate solution is 400KDa-1000KDa.
3. The method for preparing zinc hyaluronate according to claim 1, characterized in that: The mass volume ratio of sodium hyaluronate and deionized water in the sodium hyaluronate solution is 10-50 g: 200-2000 mL; The mass volume ratio of zinc chloride to deionized water in the zinc chloride aqueous solution is 1.7-13.58 g:20-50 mL; The mass ratio of sodium hyaluronate in the sodium hyaluronate solution, zinc chloride in the zinc chloride aqueous solution, and accelerator is 10-50:1.7-13.58:0.6-0.
7.
4. The method for preparing zinc hyaluronate according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution is 18-22%; The adding speed of the anhydrous ethanol is 8-10 g / min.
5. The method for preparing zinc hyaluronate according to claim 1, characterized in that: In the preparation of the accelerator, the mass fraction of the first zinc chloride aqueous solution is 9-10%; The mass fraction of sodium alginate aqueous solution is 2.5-3%; The mass fraction of the second zinc chloride aqueous solution is 7-8%.
6. The method for preparing zinc hyaluronate according to claim 1, characterized in that: In the preparation of the accelerator, the mass ratio of zeolite powder, the first zinc chloride aqueous solution, the sodium alginate aqueous solution, and the second zinc chloride aqueous solution is 10-12:120-130:130-150:90-100; The particle size of the zeolite powder is 80-120 meshes.
7. Use of zinc hyaluronate prepared by the preparation method according to any one of claims 1 to 6 in preparing skin firming products.
Citation Information
Patent Citations
Preparation method of high-molecular-weight zinc hyaluronate
CN111647100A
Preparation method and application of zinc hyaluronate
CN116948054A